Broadcast Aggregation to Improve Quality of Service in Wireless Sensor Networks. (9th March 2014) - Troubleyn, Evy; Hoebeke, Jeroen; Moerman, Ingrid; Demeester, Piet
In-network aggregation is used in wireless sensor networks to reduce energy consumption on sensor nodes with limited capabilities. Typically, only packets with the same destination are aggregated along the routing path and these packets are sent by unicast. While this is adequate for traditional multipoint-to-point sensor network applications, this is not suitable when wireless sensor nodes are connected in a full mesh topology, as isthe case in the Internet of Things. In these full mesh topologies, queues will be filled with packets with many different destinations, which limits the aggregation possibilities. Furthermore, the Quality of Service level will decrease since packets have to wait longer to find aggregation candidates. Therefore, in this paper, we propose to use broadcast aggregation that can aggregate packets independent of their destination. Broadcast aggregation is analyzed through simulations against unicast aggregation and no aggregation. Results show that energy can be reduced up to 13% compared with unicast aggregation and up to 27% compared with no aggregation. In terms of reliability, the Quality of Service is improved up to 15% compared with unicast aggregation and up to 23% compared with no aggregation. The delay on its turnis decreased by 52% compared with unicast aggregation.